Mice with humanized-lungs and immune system - an idealized model for COVID-19 and other respiratory illness - Sujit Pujhari (Taylor & Francis Group, 2020)
Lack of an appropriate animal model to study severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the etiological agent responsible for COVID-19 pandemic disease, represents a significant hurdle in the process of understanding disease biology and evaluating therapeutic and preventive candidates. It is time for public health agencies to revisit regulation on transplantation of human pluripotent stem cells for the possibility of the development of a humanized mice model with a humanized lung.